Monitoring Carbon Dioxide in the Atmosphere and Heavy Metals in Runoff Water at Active Landfill, Retired Landfill, and Forest Control Sites to Determine Remediation Effectiveness - Zolkowski, Jeshanah Jean; Banick, Jesse; Lenz, Kathryn; Sanders, Jonathan (Proceedings of the Wisconsin Space Conference, 2017)
With the exponential growth of the human population and the focus on â€œWesternizingâ€ the globe, waste and landfill use has spread. This makes the search for better remediation methods imperative. This paper describes the environmental impact of an active and a retired landfill. Carbon dioxide levels in ambient air and heavy metal concentrations in runoff water were monitored at both landfills and a control site. Data showed a significant difference in carbon dioxide levels among the sites, with the active landfill having the highest concentration and the control site having the lowest. Heavy metal tests revealed higher concentrations of lead and copper at the retired landfill compared to the active landfill and control site. The collected data is not sufficient to make a broad conclusion about remediation effectiveness; therefore, the researchers encourage continued investigation of this topic. Â 